Crystalline perfection, third-order nonlinear optical properties and optical limiting studies of 3, 4-Dimethoxy -4′-methoxychalcone single crystal. (July 2016) - Patil, P.S.; Maidur, Shivaraj R.; Rao, S. Venugopal; Dharmaprakash, S.M.
Abstract: Transparent good quality single crystals of organic nonlinear optical material, 3, 4-Dimethoxy -4 ′ -methoxychalcone (DMMC) were grown by slow evaporation solution growth technique in acetone at ambient temperature. The lattice parameters were estimated from powder X-ray diffraction. The crystalline perfection has been evaluated by high resolution X–ray diffractometry (HRXRD). The UV–vis-NIR absorption spectrum reveals that the crystal is transparent between 440 nm and 900 nm for optical applications. The fluorescence spectrum shows a peak at about 482 nm and indicates that the crystal has a blue fluorescence emission. The third order nonlinear optical properties of solution of DMMC in N, N-Dimethylformamide (DMF) solvent has been investigated using Z-scan technique with femtosecond (fs) Ti:sapphire laser pulses at 800 nm wavelength. The calculated values of nonlinear refractive index, nonlinear absorption coefficient, and the magnitude of third-order susceptibility are of the order of − 7.7×10 -14 cm 2 /W, 1.7×10 −9  cm/W and 6.7×10 −12  e.s.u. respectively. The two photon absorption (2PA) cross section and molecular second-order hyperpolarizability values obtained is of the order of 10 − 49  cm 4  s/photon/molecule and 2.8×10 −31 e.s.u. respectively. The crystal shows optical-limiting (OL) effects for femtosecond laser pulses at 800 nm. The results suggest that the nonlinear properties investigated for DMMC are comparable with some of the reported chalcone derivatives and can be desirable for nonlinear optical applications. Highlights: Good quality crystals of DMMC were grown by slow evaporation solution growth method. HRXRD results confirm that the crystalline perfection is reasonably good. The values of χ R ( 3 ) and χ I ( 3 ) are −6.616×10 −12  esu and 0.926×10 −12  esu, respectively. The nonlinear absorption, which originates from 2PA is responsible for the optical limiting action.